E-Voting Application Security Using Web-Based Cryptography RSA type: E-Voting Application Security Using Web-Based Cryptography RSA type - Istiarati Ayustina Anjaswari; Septi Andryana; Aris Gunaryati (Jurnal Mantik, 2020)
In 2017 we held the election of the chairman of the Youth South Manggarai in a conventional way, Which were displayed many members who did not came.There are many causes that are still unused ballots and the results of the voting are calculated Relatively long Also have a risk in the results of voting. With the existence of such contradictions, then to Utilize technology has been developed that makes the Electronic Voting author system.However application, the public did not trust e-voting, there will be manipulation of the results approved by each candidate. For that reason, the system can guarantee results of voting using RSA security, public key and private key to approve when you do the voting. Built using the method with waterfall SDLC. The validation test results concluded that the system is valid. Algorithm testing is done by the user entering the first odd value of 15 and the second odd value of 13 getting the value of m 168 and public key 169 from the calculation of the FPB the which is Relatively prime to m. If the public key is inputted Correctly then the user can vote.The voting results show that candidate # 2 has 32 votes, the candidate 1 has 20 votes and the others is non-voters.